Fractional flow reserve and instantaneous wave-free ratio in coronary artery bypass grafting: a meta-analysis and practice review - Abbasciano, R. G.; Layton, G. R.; Torre, S.; Abbaker, N.; Copperwheat, A.; Lucarelli, C.; Bhandari, S.; Nijjer, S.; Mikhail, G.; Casula, R.; Zakkar, M.; Viviano, A. (Frontiers in Cardiovascular Medicine, 2024)
Fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR) are invasive methods to assess the functional significance of intermediate severity coronary lesions. Both indexes have been extensively validated in clinical trials in guiding revascularisation in patients with stable ischemic heart disease undergoing percutaneous coronary intervention (PCI) with improved clinical outcomes. However, the role of these tools in coronary artery bypass grafting (CABG) is less clear.A meta-analysis of randomized trials and observational studies was carried out to help in determining the optimal strategy for assessing lesion severity and selecting graft targets in patients undergoing CABG. Electronic searches were carried out on Embase, MEDLINE and Web of Science. A group of four authors independently screened and then assessed the retrieved records. Cochrane's Risk of Bias and Robins-I tools were used for bias assessment.A survey was conducted among surgeons and cardiologists to describe current attitudes towards the pre-operative use of functional coronary investigations in practice.Clinical outcomes including mortality at 30 days, perioperative myocardial infarction, number of grafts, incidence of stroke, rate of further need for revascularisation and patient-reported quality of life did not differ in CABG guided by functional testing from those guided by traditional angiography.The survey revealed that in half of the surgical and cardiology units functional assessment is performed in CABG patients; there is a general perception that functional testing has improved patients care and its use would clarify the role of moderate coronary lesions that often need multidisciplinary rediscussing; moderate stenosis are felt clinically relevant; anatomical considerations need to be taken into account together with functional assessment.At present, the evidence to support the routine use of functional testing in intermediate lesions for planning CABG is currently insufficient. Pooled data currently available do not show an increased risk in mortality, myocardial injury, stroke in the FFR/iFR guided group. Further trials with highly selected populations are needed to clarify the best strategy.